Testicular Leydig cell tumor in a 64-year old man with cytological high grade features and no metastasis - Matthew Crabtree; Doris Cheng; Luciano Barajas (Elsevier, 2021)
Leydig cell tumor is an uncommon and often benign sex-cord stromal tumor of the testis. We present a case of a 64-year old with a testicular mass with uncharacteristically high-grade cytology and ultrasound imaging which after excision was diagnosed as an LCT and pathologically staged as T1M0.  Literature review suggested that features observed in this tumor (high mitotic rate, necrosis, atypical nuclear features, ultrasonographic heterogeneity), may place it among the 10% of LCTs that are malignant, yet its staging proved otherwise.  Hence, we set out to describe this tumor in detail and review the differential diagnosis.  The immunohistochemical profile of this tumor (positive for alpha-inhibin, calretinin, Melan-A, and cytokeratin AE1/AE3, and negative for OCT4 and podoplanin) proved valuable in making the diagnosis.